The dawdle, dally and delay of diabetic ketoacidosis: Decoding the emergency department length of stay – A chart review - Raees Gangat; Nicholas J. Dufourq; Duncan M. Havenga (Journal of the Colleges of Medicine of South Africa)
Background: Diabetic ketoacidosis is a life-threatening complication requiring prompt intervention. Understanding factors influencing the duration of emergency department (ED) stay is essential for optimising patient care and resource utilisation.